Effects of Adding Zero Valent Iron on the Anaerobic Digestion of Cow Manure and Lignocellulose - Men, Yu; Zheng, Lei; Zhang, Lingling; Li, Zifu; Wang, Xuemei; Zhou, Xiaoqin; Cheng, Shikun; Bao, Wenjun (Frontiers in Bioengineering and Biotechnology, 2020)
Previous studies showed that adding zero valent iron (ZVI) can increase methane production and degradation rate of organic waste by improving the performance of anaerobic digester. However, our study firstly showed that ZVI (37 μm, 10 g/L) inhibited the anaerobic digestion (AD) of cow manure and lignocellulose. ZVI significantly increased the methanogenic rate of cow manure in the first six days, but decreased the accumulative methane yield and accumulative volatile fatty acids yield by 10.3% and 12%, respectively. The effect of ZVI on AD of liquid biomass separated from cow manure was positive, but the effect on solid biomass was negative. These results indicate that ZVI enhanced the AD of easily biodegradable part in cow manure but inhibited the biodegradation of refractory part (lignocellulose). By analyzing the varying effects of ZVI in diverse anaerobic systems, it was found that the effects influenced by the characteristic of substrate and inoculum-substrate ratio. This study suggested that only proper ZVI addition can improve the AD process depending on the feeding materials.